ANALISA PENGARUH RASIO CAR, BOPO, LDR, NIM, DAN NPL TERHADAP ROA PADA 27 BANK YANG TERDAFTAR DI OJK TAHUN 2012-2017 - Sigit Dani Nugroho; Sintia Ananda (LPPM Universitas Asa Indonesia, 2018)
This is due to both the poor health of banks will affect the confidence the parties related to the bank as the bank's depositors, shareholders, government, Bank Indonesia and the general public. This study aimed to analyze the influence of Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), ROA, Net Interest Margin (NIM) and the Loan to Deposit Ratio (LDR) to the Return On Asset (ROA) 27 Banks in financial authorized body namely OJK during the periods of December 2012-December 2017. Data obtained from the Quarterly Financial Report and Annual Report published in OJK website. The conclusion of this study is that simultaneously, the ratio of CAR, BOPO, LDR, NIM and NPL has a significant effect on ROA. whereas, partially through the F test said that the CAR ratio has no significant effect on ROA, while the BOPO and NPL ratios have a significant negative effect and the NIM and LDR ratios have a positive effect on ROA. besides, obtained R2 value of 0.858443 or 85.8% means 85.8% variation of the dependent variable that is Return on Assets can be explained by the independent variables CAR, BOPO, LDR, NIM, and NPL that are included in this study, while the remaining 14.2% is influenced by other variables not included in this study. Other variables that affect a value, such as Opinational Profit Growth (PLO) and Credit Growth (PK).